Intentions on contraception use and its associated factors among postpartum women in Aksum town, Tigray region, northern Ethiopia: a community-based cross- sectional study - Teklehaymanot Huluf Abraha; Hailay Siyum Belay; Getachew Mebrahtu Welay (BMC, 2018)
Abstract Background Increased access to contraceptive methods has been established as a cost-effective strategy for developing countries to reduce maternal and child mortality. Intentions to contraceptive uptake appear to be best predictors of actual contraceptive practice than the unmet need. However, intention to contraceptive use in Ethiopia particularly among postpartum women is not well assessed. Therefore, the objective of this study was to assess intention to use modern contraceptive and to identify factors associated among postpartum women in Aksum town. Methods A community -based analytical cross-sectional study design was done to collect the data from 604 postpartum mothers using a structured questionnaire. The data was collected from March 25 to April 24, 2015. A multivariable logistic regression was conducted to assess factors associated with intentions to use contraceptive methods. Factors influencing intentions on contraceptive methods use were assessed by computing adjusted odds ratios (AOR) at 95% confidence interval (CI) with statistical significant p- value < 0.05. Results Intention to use modern contraceptive was 84.3%. Resumed sexual intercourse (AOR = 1.78; 95% CI: 1.34, 3.92) and women whose their husband approved family planning to use (AOR = 1.57; 95% CI: 2.02, 5.57) were more likely to have intention on contraceptive use. In addition, those women who knew at least one method of modern contraceptive (AOR = 5.17; 95% CI: 1.69, 15.82) were more likely to had intention to use modern contraceptive during extended postpartum period compared to their counterparts. Conclusion and recommendation More than eight in ten study participants have intention to use contraceptive in the Aksum town. Resumed sexual intercourse, husband's approval of family planning and knew at least one method of contraceptive are the three major predictors to be an areas when considering interventions to increase of intention on contraceptive. Therefore, this study highlighted that; in order to increase intention and adoption of contraceptive, the family planning services providers and programmers should continue the promotion of partner involvement and increasing family planning knowledge through printed media and mass media.